Development of soap formulation from agarwood essence using Taguchi method - Nur Munirah Najwa Nazri (2024)
This study was focuses on the development of an innovative bio soap formulation that combines the distinct uniqueness of agarwood through the Taguchi method approach. This approach is applied to optimize the formulation factors involving the exact concentration of agarwood, the type of base oil, and the percentage of additional ingredients in the soap formulation. The experiment was conducted by planning a structured experiment using the Taguchi Design of Experiment, and the data obtained was analysed to identify the optimal formulation combination that produced soap with the desired properties. This approach enables systematic factor analysis, reduces the need for repeated testing and leads to better efficiency in the soap formulation development process. The results from this analysis form the basis for an in-depth understanding of how different formulations affect the physical and chemical characteristics of soap, including pH, softness, and aroma. By using the Taguchi method, we can determine the key factors that have a significant impact on the quality of the soap produced. The use of Hedonic Tests was also held to evaluate appearance, texture, aroma, and colour, serving as an important indicator to measure the preferences and subjective perceptions of participants regarding soap formulations obtained from agarwood essences using the Taguchi method. The results of this study are expected to provide insightful guidance for the soap manufacturing industry to produce high quality products with special emphasis on the definite benefits of agarwood. In conclusion, this study brings an important contribution to the understanding of the development process of effective soap formulations, with the hope of producing a product that does not meet the basic needs of cleaning, but also offers an exclusive experience with unique additional benefits through the use of agarwood essence. The optimization of conditions through the Taguchi Method further ensures the production of soap formulations at their peak performance.